Politeness Strategy used by Najwa Sihab in Asking Questions on "Narasi- Eksklusif: Prabowo Subianto Bicara" - Hermawanto, Kiki Noventri; Santoso, Dwi (Journal Corner of Education, Linguistics, and Literature, 2024)
This study research aimed to describe and analyze the Politeness Strategies applied in Mata Najwa Talk Show in Asking Questions. This study used a qualitative research design to analyze and explore the politeness strategies used by the interviewer in asking questions on Narasi Mata Najwa Talk Show specific in episode “Narasi- Eksklusif: Prabowo Subianto Bicara”. The interviewer in this study was Najwa Shihab as a host to Prabowo Subianto (Indonesia Defense Minister and Politician) as a guest. The data in this study were in the form of utterances that contain politeness strategies. The result showed that the host not only used positive politeness strategy when asking questions but also used a negative politeness strategy. The interviewer used two types of politeness strategy in asking questions so the viewer of the show can get two sides of guest point of view. From the analysis of the data, the findings of the study revealed that the interviewer employed two main strategies of politeness, namely Positive Politeness (73%) and Negative Politeness (27%).